Childhood Adversity and Developmental Effects 2015
DOI: 10.1201/b18372-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Child Maltreatment in a Representative Sample of the German Population

Abstract: Background: Representative data about the frequency of child maltreatment is needed in order to estimate the extent of the problem in the wider population as well as to provide the basis for interpretation of frequency rates in clinical samples. However, previous representative studies on the frequency of child maltreatment in Germany and other countries were limited as they focused on the assessment of physical and sexual abuse whilst emotional forms of maltreatment were ignored. In addition, previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(10 reference statements)
1
3
1
1
Order By: Relevance
“…Consistent with many other studies, our results found females to be at greater risk for sexual abuse of all types compared with males (Häuser et al, 2011; Iffland et al, 2013; Pereda et al, 2009; Sethi et al, 2013; Stoltenborgh et al, 2011). It must be noted, however, that a higher proportion of female victims does not hold true in all contexts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with many other studies, our results found females to be at greater risk for sexual abuse of all types compared with males (Häuser et al, 2011; Iffland et al, 2013; Pereda et al, 2009; Sethi et al, 2013; Stoltenborgh et al, 2011). It must be noted, however, that a higher proportion of female victims does not hold true in all contexts.…”
Section: Discussionsupporting
confidence: 93%
“…So far, no studies have examined the co-occurrence of different types of maltreatment in institutions, but from research on abuse in general, it is known that such co-occurrence is the rule rather than the exception, and can be up to 95% (Finkelhor, Ormrod, & Turner, 2007; Herrenkohl & Herrenkohl, 2009). In this study, the overall prevalence of co-occurring types of victimization (0.9%) was slightly lower than what has been reported by other studies using representative samples, which found from 3.3% for the co-occurrence of two different types of child maltreatment to 0.1% for the co-occurrence of five different types (Häuser et al, 2011; Iffland et al, 2013). This in part is due to the fact that in the present study, the assessment of sexual abuse as well as other forms of violence was limited to victimization within institutions.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This 25item scale distinguishes between five types of childhood trauma: emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect. The presence of moderate to severe early life stress was assumed if respondents scored at or above specific validated cut-offs on at least one of the five subscales (13).…”
Section: Methodsmentioning
confidence: 99%
“…Even though the measure is quite simple, there is some evidence that the three items led to reliable results. Iffland et al (2013) used the Childhood Trauma Questionnaire (CTQ) by Bernstein et al (2003) in a large representative sample from the German population (N = 2500). The prevalence rates found in this study (emotional abuse: 10%; physical abuse: 12%; sexual abuse: 6%) are close to the rates of the present study (emotional abuse: 11%; physical abuse: 9%; sexual abuse: 10%).…”
Section: Limitationsmentioning
confidence: 99%